Apocynin Improves Insulin Resistance through Suppressing Inflammation in High-Fat Diet-Induced Obese Mice. (21st February 2011) - Meng, Ran; Zhu, Da-Long; Bi, Yan; Yang, Dong-Hui; Wang, Ya-Ping
Abstract : We investigated the effects of apocynin on high-fat diet- (HFD-) induced insulin resistance in C57BL/6 mice. After 12 weeks of HFD, the mice that exhibited insulin resistance then received 5 weeks of apocynin (2.4 g/L, in water). Following apocynin treatment, fasting glucose, insulin, and glucose tolerance test showed significant improvement in insulin sensitivity in HFD-fed mice. We demonstrated that serum levels of tumor necrosis factor-α (TNF-α ), interleukin-6 (IL-6), and leptin were remarkably reduced with apocynin treatment. We also found that mRNA expression of TNF-α, IL-6, and monocyte chemoattractant protein-1 (MCP-1) in the liver and mRNA expression of TNF-α, IL-6, MCP-1, and leptin in adipose tissue were suppressed by apocynin. Furthermore, the activity of transcription factor NF-κ B in the liver was significantly suppressed with apocynin treatment. These results suggest that apocynin may reduce inflammatory factors in the blood, liver, and adipose tissue, resulting in amelioration of insulin resistance in HFD-fed mice.